Pengaruh Kompetensi Terhadap Kinerja Pegawai Badan Pengelola Keuangan Dan Aset Daerah Kabupaten Karangasem: Peran Mediasi Kepuasan Kerja Dan Komitmen Organisasi - Ida Ayu Putu Sugiartini; I Putu Santika; I Made Petrus; Ni Luh Sili Antari (Warmadewa Management and Business Journal (WMBJ), 2026)
This study aims to analyze the effect of competence on employee performance at the Regional Financial and Asset Management Agency of Karangasem Regency: The Mediating Role of Job Satisfaction and Organizational Commitment. The population of this research consists of all 81 employees at BPKAD Karangasem. The sampling technique used is a census or saturated sampling. The data analysis techniques include validity testing, reliability testing, classical assumption testing, and path analysis. The results show that: (1) competence has a positive and significant effect on job satisfaction, organizational commitment, and employee performance; (2) job satisfaction has a positive and significant effect on employee performance; (3) organizational commitment has a positive and significant effect on employee performance; (4) job satisfaction does not mediate the effect of competence on employee performance; and (5) organizational commitment does not mediate the effect of competence on employee performance at BPKAD Karangasem. The study suggests that the leadership of BPKAD Karangasem should enhance employee competence, job satisfaction, organizational commitment, and performance. This can be achieved through soft skills training, evaluation and adjustment of performance allowances, development of clear career path planning, providing recognition for years of service, and offering platforms for employees to express ideas, suggestions, or solutions through periodic discussion forums or idea submission platforms.